Phytotoxic metabolites from Neofusicoccum parvum, a pathogen of Botryosphaeria dieback of grapevine. (July 2015) - Abou-Mansour, Eliane; Débieux, Jean-Luc; Ramírez-Suero, Montserrat; Bénard-Gellon, Mélanie; Magnin-Robert, Maryline; Spagnolo, Alessandro; Chong, Julie; Farine, Sibylle; Bertsch, Christohpe; L'Haridon, Floriane; Serrano, Mario; Fontaine, Florence; et al.
Abstract : Graphical abstract: Thirteen phytotoxins were identified from Neofusicoccum parvum . Analysis of grapevine wood from plants showing botryosphaeria dieback symptoms revealed the presence of two of the isolated phytotoxins. Highlights: Investigation of thirteen isolates of Neofusicoccum parvum for phytotoxins. Thirteen compounds belonging to four different chemical families were isolated. Phytotoxic activity was evaluated through leaf disc assay. Investigation the expression of defence-related genes in cells in response to terremutin. Presence of two phytotoxins in grapevine wood of plants showing symptoms. Abstract: Liquid chromatography-diode array screening of the organic extract of the cultures of 13 isolates of the fungus Neofusicoccum parvum, the main causal agent of botryosphaeria dieback of grapevine, showed similar metabolites. One strain was selected for further chemical studies and led to the isolation and characterisation of 13 metabolites. Structures were elucidated through spectroscopic analyses, including one- and two-dimensional NMR and mass spectrometry, and through comparison to literature data. The isolated compounds belong to four different chemical families: five metabolites, namely, (−)-terremutin (1 ), (+)-terremutin hydrate (2 ), (+)- epi -sphaeropsidone (3 ) (−)-4-chloro-terremutin hydrate (4 ) and(+)-4-hydroxysuccinate-terremutin hydrate (5 ), belong to the family of dihydrotoluquinones; two metabolites, namely, ( 6S, 7R ) asperlin (6 ) and ( 6R, 7S )- dia -asperlin (7 ), belong to the family of epoxylactones; four metabolites, namely, ( R )-(−)-mellein (8 ), ( 3R, 4R )-4-hydroxymellein (9 ), ( 3R, 4S )-4-hydroxymellein (10 ) ( R )(−)-3-hydroxymellein (11 ), belong to the family of dihydroisocoumarins; and two of the metabolites, namely, 6-methyl-salicylic acid (12 ) and 2-hydroxypropyl salicylic acid (13 ), belong to the family of hydroxybenzoic acids. We determined the phytotoxic activity of the isolated metabolites through a leaf disc assay and the expression of defence-related genes in Vitis vinifera cells cv. Chardonnay cultured with (−)-terremutin (1 ), the most abundant metabolite. Finally, analysis of the brown stripes of grapevine wood from plants showing botryosphaeria dieback symptoms revealed the presence of two of the isolated phytotoxins.